2005
DOI: 10.1021/jp054422c
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Uranyl−Nitrile Complex Ions

Abstract: Electrospray ionization was used to generate doubly charged complex ions composed of the uranyl ion and nitrile ligands. The complexes, with general formula [UO2(RCN)n]2+, n = 0-5 (where R=CH3-, CH3CH2-, or C6H5-), were isolated in an ion-trap mass spectrometer to probe intrinsic reactions with H2O. For these complexes, two general reaction pathways were observed: (a) the direct addition of one or more H2O ligands to the doubly charged complexes and (b) charge-reduction reactions. For the latter, the reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
80
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(92 citation statements)
references
References 42 publications
12
80
0
Order By: Relevance
“…12 The binding energies for these complexes are 26.5 and 23.7 kcal/mol, respectively. This suggests that a ligand addition with a binding energy greater than 23.7 kcal/mol should be observable in mass spectroscopic studies.…”
Section: +mentioning
confidence: 97%
See 1 more Smart Citation
“…12 The binding energies for these complexes are 26.5 and 23.7 kcal/mol, respectively. This suggests that a ligand addition with a binding energy greater than 23.7 kcal/mol should be observable in mass spectroscopic studies.…”
Section: +mentioning
confidence: 97%
“…[9][10][11] Over the last couple of years, Groenewold and co-workers published results of measurements on various uranyl complexes in the gas phase. [12][13][14][15][16][17] These experiments provide the computational chemistry community with a wealth of experimental benchmark data that can be used as a proving ground for the current computational methodologies and to improve upon them. In a series of joint experimental and computational papers 13,[18][19][20][21] it was shown that vibrational stretching frequencies of the actinide species and the relative energetics calculated with density functional theory (DFT) are in good agreement with experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Average values were also used in the case of [UO 2 (Pn) 4 . 9 Again, there is only one instance for which the water ligands outnumber the nitrile ligands.…”
Section: +mentioning
confidence: 99%
“…This effect occurs for ligand additions to both the dicationic and the monocationic species and can explain the large number of dicationic complexes with mainly nitrile ligands observed experimentally. 9 In addition to ligand addition reactions, charge-exchange or hydrolysis reactions of the form of eqs 3 and 4 have been examined. These reactions involve at least two ligands, and water must be one of them.…”
mentioning
confidence: 99%
“…Charged uranyl coordination complexes can be formed using electrospray-ionization (ESI), which has proven to be a highly versatile means for introducing these species into the gas phase. Recent research by our group [22][23][24][25][26], that of Moulin [27,28], and Pasilis [29] have demonstrated the great utility of ESI for forming a variety of dioxouranium V and VI complexes. ESI usually produces multiple species, however, complexes of interest can be isolated on the basis of mass-to-charge ratio using selective ion ejection/storage capabilities of a trapped ion mass spectrometer.…”
mentioning
confidence: 99%